2021
DOI: 10.1016/j.redox.2021.102137
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic signaling in the modulation of redox biology

Abstract: Purinergic signaling is a cell communication pathway mediated by extracellular nucleotides and nucleosides. Tri- and diphosphonucleotides are released in physiological and pathological circumstances activating purinergic type 2 receptors (P2 receptors): P2X ion channels and P2Y G protein-coupled receptors. The activation of these receptors triggers the production of reactive oxygen and nitrogen species and alters antioxidant defenses, modulating the redox biology of cells. The activation of P2 receptors is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 181 publications
2
30
0
2
Order By: Relevance
“…Studies have shown theophylline and adenosine to compete for adenosine receptor when given in combination [29]. It is also known that activation of adenosine receptor after binding with adenosine reduces ROS [30,31]. In this context, we studied the levels of ROS after treatment with theophylline and adenosine (200 µmol/l).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown theophylline and adenosine to compete for adenosine receptor when given in combination [29]. It is also known that activation of adenosine receptor after binding with adenosine reduces ROS [30,31]. In this context, we studied the levels of ROS after treatment with theophylline and adenosine (200 µmol/l).…”
Section: Resultsmentioning
confidence: 99%
“…The nucleoside adenosine is a metabolite that elicits coronary vasodilation. Furthermore, it was demonstrated that in hypoxic conditions, under energy depletion, cellular levels of adenosine increase, eliciting an antioxidant activity by inducing antioxidant enzymes activity [50,51]. As a result, adenosine has been extensively investigated for its cardioprotective effects, with controversial results in-vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Also, ATP directly activates the plasma membrane channel P2X7 receptor (P2X7R), leading to an intracellular influx of potassium ions, key triggers which activate the NOD-like receptor thermal protein domain associated protein 3(NLRP3) inflammasome. Simultaneously in the mitochondria, ROS and ATP production are coupled to regulate cellular redox reactions [ 57 ]. In healthy tissue stroma, levels of ATP and its metabolite adenosine are negligible, while their accumulation is significantly increased in inflammatory or tumor microenvironments [ 58 ].…”
Section: Oxidative Stress Stimulates Damp Release and Worsens Vitiligomentioning
confidence: 99%